Donor lymphocyte infusions: An experience from a tertiary care center of North India - Divjot Singh Lamba; Parmatma Prasad Tripathi; Rekha Hans; Alka Khadwal; Ratti Ram Sharma (Asian Journal of Transfusion Science)
Donor lymphocyte infusions (DLIs) are often recommended products after allogeneic hematopoietic stem cell transplant to increase graft – versus – leukemia effect. More success rate of DLI has been reported in relapsed posttransplant chronic myeloid leukemia. Whatever the indication for DLI, mortality related to post-DLI infusion is 5%–20%, and more than one-third of patients will develop acute and/or chronic graft versus host disease (GVHD) after DLI. We report two cases where DLIs were used for residual disease after posttransplant. Both of DLI went uneventful. None of the patient’s developed signs of GVHD postinfusion. Although both patients expired with different causes, none were related to DLI infusion. Information from published literature suggests that DLI should be administered early after relapse or as a prophylactic strategy in patients receiving T-cell-depleted grafts, and patients with aggressive diseases may benefit from disease reduction before DLI. However, further evidence is required to evaluate its efficacy, especially in relapsed or residual hematological malignancies.